2020
DOI: 10.1101/2020.12.22.424024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dynamic evolution of the MutS family in animals: multiple losses of MSH paralogues and gain of a viral MutS homologue in octocorals

Abstract: MutS is a key component of the Mismatch Repair (MMR) pathway. Members of the MutS family of proteins are present in bacteria, archaea, eukaryotes, and viruses. Six MutS homologues (MSH1-6), have been identified in yeast, three of which function in nuclear MMR, while MSH1 has been associated with mitochondrial DNA repair. MSH1 is believed to be lacking in animals, potentially reflecting the loss of MMR in animal mitochondria, and correlated with higher rates of mitochondrial sequence evolution. An intriguing ex… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Second, we found the same domain composition of mtMutS as Bilewitch et al [6], but provided evidence for the presence of an additional domain -"MutS IV" or the clamp domain -in 12 octocoral species. Interestingly, the "MutS IV" domain also shows an intermittent presence in other MutS proteins, like MSH1 [10]. Third, the functionally important amino-acids identified in [6] were well conserved in the expanded dataset, with a few exceptions.…”
Section: Sequence Changes In Mtmuts Of Octocoral Species With Acceler...mentioning
confidence: 98%
See 1 more Smart Citation
“…Second, we found the same domain composition of mtMutS as Bilewitch et al [6], but provided evidence for the presence of an additional domain -"MutS IV" or the clamp domain -in 12 octocoral species. Interestingly, the "MutS IV" domain also shows an intermittent presence in other MutS proteins, like MSH1 [10]. Third, the functionally important amino-acids identified in [6] were well conserved in the expanded dataset, with a few exceptions.…”
Section: Sequence Changes In Mtmuts Of Octocoral Species With Acceler...mentioning
confidence: 98%
“…Of these, three proteins -MSH2, MSH3, and MSH6 -function in nuclear MMR, while MSH4 and MSH5 function in meiotic recombination [7]. Recently, we found that an ortholog of yeast MSH1, a MutS protein targeted to mitochondria and involved in mitochondrial DNA repair [8,9], is present in Hexacorallia, the sister group of octocorals, as well as two other phyla of non-bilaterian animals [10]. While the role of animal MSH1 has not been experimentally elucidated, its conserved structure, orthology to yeast MSH1, and inferred mitochondrial localization suggest a similar role in mitochondrial DNA repair [10].…”
mentioning
confidence: 99%
“…[6], but provided evidence for the presence of an additional domain – “MutS IV” or the clamp domain – in 12 octocoral species. Interestingly, the “MutS IV” domain also shows an intermittent presence in other MutS proteins, like MSH1 [10]. Third, the functionally important amino-acids identified in [6] were well conserved in the expanded dataset, with a few exceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, three proteins – MSH2, MSH3, and MSH6 – function in nuclear MMR, while MSH4 and MSH5 function in meiotic recombination [7]. Recently, we found that an ortholog of yeast MSH1, a MutS protein targeted to mitochondria and involved in mitochondrial DNA repair [8, 9], is present in Hexacorallia, the sister group of octocorals, as well as two other phyla of non-bilaterian animals [10]. While the role of animal MSH1 has not been experimentally elucidated, its conserved structure, orthology to yeast MSH1, and inferred mitochondrial localization suggest a similar role in mitochondrial DNA repair [10].…”
Section: Introductionmentioning
confidence: 99%